Preparing and Characterization of Some Heterocyclic Compounds with Studying Their Biological Activity - Mahmoud, Muhanned A (Al-Nahrain Journal of Science, 2018)
New compounds of (E-(1,3-bis)3-bromophenyl) prop-2-en-1-one], (E-(1-(3-Nitrophenyl-(3-(1-h-pyrrol-2-yl) prop-2-en-1-one], (E-(1-(3-Nitrophenyl-(3-(1H-pyrrol-2-yl) prop-2-en-1-one], [(E)–N,N-1,3-bis) 3-Nitrophenyl) propan-3-yl-1-ylidene) dimethan amine], (E-(1-(3-Nitrophenyl-(3-(1-H-pyrrol-2-yl) prop-2-en-1-one] and [(E-(1,3-bis)4-dimethylamino) phenyl) prop-2-en-1-one] have been synthesized. The prepared compounds have synthesized from chalcone [1] and characterized by using FT-IR, Uv/ vis and 1H-NMR spectra besides, determining the melting points and Rf with the biological activity.